ANALISIS FAKTOR AKSES PERMODALAN, PENGGUNAAN FINANCIAL TECHNOLGY, DAN LITERASI KEUANGAN TERHADAP KEBERLANJUTAN USAHA UMKM DI SHELTER MANAHAN - Ayu Febriana; Djoko Kristianto (Jurnal Nirta : Inovasi Multidisiplin, 2026)
This study aims to analyze the effect of access to capital, the use of financial technology, and financial literacy on the business sustainability of Micro, Small, and Medium Enterprises (MSMEs) at Shelter Manahan, Surakarta City. Business sustainability is a crucial factor in supporting regional economic growth and improving the welfare of MSME actors. This research employs a quantitative approach using primary data collected through questionnaires distributed to MSME owners at Shelter Manahan. The sample consists of 100 respondents selected using a non-probability sampling method. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS software. The results indicate that access to capital has a positive and significant effect on MSME business sustainability. Furthermore, the use of financial technology also has a positive and significant effect on business sustainability. Financial literacy is proven to have a positive and significant impact on the sustainability of MSMEs. These findings suggest that easier access to capital, effective utilization of financial technology, and good financial knowledge and management capabilities can enhance the ability of MSMEs to maintain and develop their businesses sustainably. Therefore, support from the government and financial institutions is needed to improve access to capital, promote the use of financial technology, and enhance financial literacy among MSME actors.